Penggunan Media Pembelajaran Video untuk Solusi Penurunan Pemahaman Materi Pembelajaran Ketika Belajar Online Akibat Pandemic Covid-19 - Febni Suasty; Ahmad Alfian Hadi (Milenial: Journal for Teachers and Learning, 2020)
Recent COVID-19 pandemic has forced people to minimize outdoor activities to avoid increasingly massive spread of the virus, including schools in Indonesia. Government has established a policy that learning activities must be carried out online. In fact, based on a literature review conducted by researchers, online learning is a new thing for some students and teachers in Indonesia, which might cause learning materials are not maximally delivered. Students are very likely to feel bored which presumably have an impact on decreased understanding of learning materials. One of alternative choices for teachers is using learning videos as interesting learning media which are then followed by teacher explanations so that students are able to understand materials provided better. Video is a media or tool that provides audio and visuals that contain learning messages covering concepts, principles, procedures, and theories of knowledge application. In addition, video is one of the excellent media in delivering materials in the context of online learning nowadays. It is expected to increase understanding of materials whose process takes place asynchronously, in which students can learn at any time.